When Journalists See Themselves as Villains: The Power of Negative Discourse. (September 2021) - Moon, Ruth
This article examines the way journalists talk about themselves and negotiate authority with sources, audiences, and media policy in a postconflict, developmental authoritarian state. Grounded in concepts of metajournalistic discourse and authority, the study shows how members of the journalism field in some contexts embrace a narrative that limits autonomy and situates them as untrustworthy social actors. Interviews collected over a 7-month period in Rwanda show that a shared sense of untrustworthiness defines the contemporary boundaries of the Rwandan journalism field. The findings also suggest that consensus-oriented or postconflict social contexts might encourage journalists to adopt less autonomous social roles.